Characteristics of Posterior Ethmoidal Artery and Its Relationship with Anterior Ethmoidal Artery and Skull Base on CT Scan - Thuy Chung TRAN PHAN; Kiet Vuong DANG (Medeniyet Medical Journal)
Objective: Investigation of the anterior and posterior ethmoidal arteries on computed tomography (CT) scans of the sinuses before and during surgery is important, especially for inexperienced surgeons. The aim of this study was to examine the anatomical characteristics of the posterior ethmoid artery in Vietnamese and the distance from the posterior ethmoid artery to the anterior ethmoid artery and the skull base on CT scan. Methods: A cross-sectional study was conducted involving patients aged ≥18 years who underwent CT scan imaging at the Ear, Nose and Throat Hospital of Ho Chi Minh City from February 2023 to July 2023. Results: There were 100 patients in this study, of whom 51% (51/100) were female and 49% (49/100) were male. Patient ages ranged from 20 to 84 years. Their average age was 40.92+-14.65 years. The distance on CT scan between the posterior and anterior ethmoidal arteries was 13.98+-1.95 mm (9.3 to 18.6 mm). This distance in males was significantly higher than female (p=0.001). However, there is no difference in this distance between the left and right side (p=0.67). The distance between the posterior ethmoid artery and skull base ranged from 0 to 5.4 mm. The average distance between the posterior ethmoidal artery and skull base on CT scan was 0.95+-0.94 mm. The diameter of the posterior ethmoid artery was 0.57-0.91 mm. The average diameter of the posterior ethmoidal artery on CT scan was 0.76+-0.09 mm. Conclusion: The characteristics of the posterior ethmoid artery should be considered when examining the CT scan. Distance from the posterior ethmoid This study provides useful information on the characteristics of the posterior ethmoid artery on CT scans, which can be applied in endoscopic sinus surgery and skull base surgery.